A Pursuit Problem in an Infinite System of Second-Order Differential Equations - Ibragimov, G.; Allahabi, F.; Kuchkarov, A. (Український математичний журнал, 2013)
We study a pursuit differential game problem for an infinite system of second-order differential equations. The control functions of players, i.e., a pursuer and an evader are subject to integral constraints. The pursuit is completed if z(τ) = z˙ (τ) = 0 at some τ > 0, where z(t) is the state of the system. The pursuer tries to complete the pursuit and the evader tries to avoid this. A sufficient condition is obtained for completing the pursuit in the differential game when the control recourse of the pursuer is greater than the control recourse of the evader. To construct the strategy of the pursuer, we assume that the instantaneous control used by the evader is known to the pursuer. Вивчається проблема переслідування в диференціальній rpi для нескінченної системи диференціальних рівнянь другого порядку. Керівні функції гравців, тобто переслідувача та переслідуваного, мають деякі обмеження. Переслідування завершується, коли z(τ) = z˙ (τ) = 0 для деякого τ > 0, де z(t) — стан системи. Переслідувач намагається завершити переслідування, а переслідуваний намагається цього уникнути. Встановлено достатню умову завершення переслідування в диференціальній грі, коли зворотнє управління для переслідувача більше, ніж для переслідуваного. Для побудови стратегії переслідувача вважаємо, що миттєве керування, застосоване переслідуваним, є відомим переслідувачу.